Hydatid cyst in unusual location: Pterygopalatine fossa–infratemporal fossa. Issue 4 (August 2016) - Şahin, Bayram; Çomoğlu, Şenol; Polat, Beldan; Değer, Kemal
Abstract: Introduction: Hydatid Cyst is a zoonotic infection most commonly caused by larvae of the Echinococcus granulosus . Humans are an accidental intermediate host following ingestion of the larvae. Case Report: We report the case of a 16-year-old male patient presenting with a hydatid cyst in the pterygopalatine fossa. There was no pulmonary or hepatic involvement. The definitive therapy comprised excision of the cystic mass and postoperative medical treatment. Discussion: Pterygopalatine fossa involvement is reported in three cases in the literature. In this report we represent a case with pterygopalatine fossa hydatid cyst extending into infratemporal fossa. Conclusion: The hydatid cyst of infratemporal and pterygopalatine fossa is extremely rare. Possibility of hydatid cyst should not be ignored at the differential diagnosis of cystic lesions in head and neck region, especially in endemic areas.